Hukuman Mati Perspektif Al-Qur'an - Herry, Musleh (UIN Maulana Malik Ibrahim Malang, 2003)
The problem of capital punishment in Indonesia as a country which has Pancasila philosophy is still a discussion which caused many different views until now. This problem arises because it is considered to be